Building Multitemporal Awareness and Reflexivity in Family Business: A Visual Sensemaking Exercise. (April 2021) - Lefebvre, Vincent; Radu-Lefebvre, Miruna; Gartner, William B.; Clarke, Jean
This article presents an exercise designed for successors and other business family members with the aim to enable them to communicate their understandings of their family and family business' past legacies and to express their future-related projections. First initiated in France in 2014, then duplicated in United States in 2019, the exercise has been used in undergraduate, graduate, and executive education courses, with national and international cohorts. While the exercise has typically focused on classes composed of successors, it has also been used in executive education courses with business family members from older and younger generations. The learning activity asks participants to draw three consecutive images of their family business—past, present, and future—to develop a visual narrative of the family and family business legacies and future. Participants are then invited to tell the story of their family business and to depict its imagined future using the three drawings as guides, within the group setting. This visual sensemaking exercise enables participants to access tacit modes of relating to past legacies and contributes to developing multitemporal awareness and reflexivity in multigenerational family businesses.